2018
DOI: 10.1029/2017jb014600
|View full text |Cite
|
Sign up to set email alerts
|

The Seismic History of the Pisia Fault (Eastern Corinth Rift, Greece) From Fault Plane Weathering Features and Cosmogenic36Cl Dating

Abstract: The deformation of the eastern Corinth rift (Greece) is distributed along several E-W trending active normal faults. Here the 25-km-long Pisia fault experienced up to 150 cm of coseismic displacement during the 1981 Alkyonides earthquake sequence (M = 6.7, 6.4, 6.3). Using terrestrial laser scanning, coupled with analyses of color changes, lichen colonization, and karstic features, we identify differentially weathered horizontal stripes on the exposed Pisia fault plane. The stripe boundaries occur at scarp hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 104 publications
(159 reference statements)
2
33
0
Order By: Relevance
“…Similar discoloured bands have been identified on other fault scarps (e.g. Giaccio et al, 2003; Mechernich et al, 2018). It follows that these bands will be more weathered than the subsurface fault scarp and, depending on the length of time (i.e.…”
Section: Preferred Model and Demarcation Of Single-event Displacementssupporting
confidence: 67%
See 4 more Smart Citations
“…Similar discoloured bands have been identified on other fault scarps (e.g. Giaccio et al, 2003; Mechernich et al, 2018). It follows that these bands will be more weathered than the subsurface fault scarp and, depending on the length of time (i.e.…”
Section: Preferred Model and Demarcation Of Single-event Displacementssupporting
confidence: 67%
“…Stewart (1996) measured the surface roughness of the Kaperelli and Pisia faults in the eastern Gulf of Corinth, both of which ruptured to the surface and exposed fresh scarp faces in the 1981 Corinth earthquakes. Mechernich et al (2018) revisited this fault using a multi-proxy approach and identified six to eight weathering bands (or stripes) that could be correlated with earthquakes. Mechernich et al (2018) revisited this fault using a multi-proxy approach and identified six to eight weathering bands (or stripes) that could be correlated with earthquakes.…”
Section: Relative-age Dating Techniquesmentioning
confidence: 99%
See 3 more Smart Citations